1995
DOI: 10.1101/gad.9.24.3051
|View full text |Cite
|
Sign up to set email alerts
|

A proline-rich TGF-beta-responsive transcriptional activator interacts with histone H3.

Abstract: The molecular mechanisms involved in the regulation of gene expression by transforming growth factor-13 (TGF-13) have been analyzed. We show that TGF-~ specifically induces the activity of the proline-rich trans-activation domain of CTF-1, a member of the CTF/NF-I family of transcription factors. A TGF-13-responsive domain (TRD) in the proline-rich transcriptional activation sequence of CTF-I was shown to mediate TGF-13 induction in NIH-3T3 cells. Mutagenesis studies indicated that this domain is not the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
149
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(159 citation statements)
references
References 61 publications
(67 reference statements)
6
149
4
Order By: Relevance
“…The C-terminal part of the TAD (amino acids 486-499) displays transcriptional activity but it is less active than the whole TAD. This region has been described previously as a TRD [9]. It is noticeable that it is not sensitive to H # O # (compared with the intact TAD).…”
Section: The N-terminal Part Of the Tad Is Required For The Regulatiosupporting
confidence: 57%
See 3 more Smart Citations
“…The C-terminal part of the TAD (amino acids 486-499) displays transcriptional activity but it is less active than the whole TAD. This region has been described previously as a TRD [9]. It is noticeable that it is not sensitive to H # O # (compared with the intact TAD).…”
Section: The N-terminal Part Of the Tad Is Required For The Regulatiosupporting
confidence: 57%
“…This cysteine, contrary to Cys-405, seems to be easily modified by either oxidizing or alkylating reagents, suggesting a different exposure of these residues within the TAD protein sequence. Moreover, this TAD has been shown to interact directly with several proteins involved in the control of transcription, such as the TATA-box-binding protein TBP [22], the co-activator CBP\ p300 [23] and the histones H1 and H3 [9,24]. This TAD was also shown to enhance synergistically the activation of transcription mediated by the oestrogen receptor [25] and the aryl hydrocarbon receptor (AhR) [10] pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies indicated that, at least in some circumstances, CTF/NF1 functions to regulate transcription via a mechanism that is likely to involve higher order chromatin structures (45,46). Such an activity would likely be missed in a transient transfection reporter gene analysis where "naked" plasmid DNA is utilized (35).…”
Section: Carg Boxes 1 and 2 Function As Recognition Sites For Srf Or mentioning
confidence: 99%